Trouble with Tattle-Tails - Auxier, Jonathan; Demidova, Olga (New York : Amulet Books, 2021)
As an employee in the Fabled Stables, young Auggie must protect all fantastical creatures, even the irritatingly talkative furry tails that have attached themselves to the human residents of Rainbow's End.
K-3
2.9
Keywords: Animals, Mythical -- Juvenile fiction; Friendship -- Juvenile fiction; Imaginary creatures -- Fiction; Friendship -- Fiction; Fantasy; Fantasy fiction